Prototype Sistem Informasi Administrasi Pengadaan Barang Dengan Teknologi RFID - Marini Marini (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2019)
Goods Procurement Administration Information System is the procurement of ATK / stock of goods as providers or suppliers of goods for smooth operations. Procurement Administration Information System Goods for recording and storing data on goods procurement often occur errors. With the information system prototype Procurement of goods by using Radio Frequency Identification (RFId) technology to be created, it is expected that the process of requesting, procuring, distributing and reporting is more useful to be applied in the future. Software Development Model namely the waterfall model and the Object Oriented Analysis Design (OOAD) model, which is data collection through interviews, observation, object analysis and documentation. The tools used in developing system analysis are Activity diagrams, Use cases, Package Diagrams, Class Diagrams, Deployment Diagrams. Administration Information Systems Procurement of Goods at PT. Bakti Timah Pangkalpinang Hospital Administrative Procurement Information System at PT. Bakti Timah Hospital Pangkalpinang is carried out using a SWOT analiss, system design is described by UML modeling, Programming Language uses VB.Net 2008 and the database uses Mysql. The results of this study are prototype information systems Procurement of goods using Radio Frequency Identification (RFId) Technology at PT. Bakti Timah Hospital Pangkalpinang.Keywords : Prototype, Procurement Administration System, Radio Frequency Identification Technology